Noise and whole-body vibration in underground locomotive operators - Southon, Sharon (My University, 2011)
Introduction Locomotive operators in the mining industry are exposed to high levels of noise and vibration. There is currently limited information indicating whole-body vibration exposure levels conducted over an 8-hour time weighted average (TWA) exposure period; most of the available data are based on instantaneous measurements. The 10-Ton New Era locomotive was specifically designed with the focus on areas such as ergonomics, safety, future automation, productivity and flexibility of use. The locomotive has a single cab and can be driven and controlled with maximum visibility in the direction of travel. Most mining houses are converting from the use of the 10 Ton Goodman battery operated locomotive to the 10Ton New Era locomotive, hence the focus of noise and vibration measurements on the latter. Objectives This research report documents a project to measure noise and whole-body vibration exposure levels of locomotive operators working in an underground platinum mine. The objectives of the study are: • to describe the eight hour time weighted average occupational noise exposure levels of locomotive operators operating the 10-Ton New Era locomotive in an underground platinum mine over 2008 and 2009; • to describe personal whole-body vibration exposure levels of locomotive operators operating the 10-Ton New Era locomotive in an underground platinum mine over 2008 and 2009; and 5 • to determine whether personal noise and whole-body vibration exposure levels of locomotive operators operating the 10-Ton New Era locomotive in an underground platinum mine over 2008 and 2009 comply with national and international standards. Methods Personal noise and whole-body vibration exposure measurements were obtained from 21 underground locomotive operators. Measurements were conducted in accordance with the procedures described in the SANS 10083 standard for personal noise dosimetry and the ISO 2631-1 standard for whole-body vibration. Determination of likely health risks for the operators were based on a comparison of the measured time-weighted noise exposure levels with the South African OEL and the ACGIH threshold limit value; whole-body vibration levels were compared with the HGCZ limits presented in Annex B of the ISO 2631-1 standard and the EU directive daily exposure limits. Results The measured noise and whole-body vibration levels taken over an 8-hour TWA exposure period were higher when compared to national and international standards. The mean LTWA levels for noise was 66.5 dB(A) with 12.5% of the measurements exceeding the South African OEL of 85dB(A). 45% of the wholebody vibration measurements fell within the HGCZ indicating that whole-body vibration exposure on locomotive operators presents a moderate probability for an adverse health outcome. Discussion and Conclusion Locomotive operators are exposed to potentially harmful levels of noise and whole-body vibration. The Mine Health and Safety Act requires an employer to assess the health and safety risks that hazards pose to their employees, and to take reasonably practicable steps towards eliminating or controlling those risks. Like any other risks at a workplace, noise and whole-body vibration needs to be 6 identified and controlled, and the approach to be taken is one of a risk management
MPH, Occupational Hygiene, Faculty of Health Sciences, University of the Witwatersrand
Keywords: noise; vibration; whole-body vibration; locomotive operators; underground